2015
DOI: 10.1099/jgv.0.000023
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an Adoxophyes orana granulovirus (AdorGV) occlusion body morphology mutant: biological activity, genome sequence and relationship to other isolates of AdorGV

Abstract: A granulovirus (GV) producing occlusion bodies (OBs) with an unusual appearance was isolated from Adoxophyes spp. larvae in the field. Ultrastructural observations revealed that its OBs were significantly larger and cuboidal in shape, rather than the standard ovo-cylindrical shape typical of GVs. N-terminal amino acid sequence analysis of the OB matrix protein from this virus suggested that this new isolate was a variant of Adoxophyes orana granulovirus (AdorGV). Bioassays of this GV (termed AdorGV-M) and an E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Such a process would enable development of a biopesticide that persists longer in the field. Repeated exposure to UV, followed by selection of active virus, has been successfully undertaken with other baculoviruses to increase UV resistance [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a process would enable development of a biopesticide that persists longer in the field. Repeated exposure to UV, followed by selection of active virus, has been successfully undertaken with other baculoviruses to increase UV resistance [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…A new variant of Adoxophyes orana granulovirus (AdorGV), designated AdorGV-M, isolated from Adoxophyes spp. larvae in the field, was shown to be as pathogenic as an English isolate AdorGV-E, and to have a five-fold longer half-life than AdorGV-E after UV irradiation [37]. The AdorGV-M isolate had significantly larger cuboidal OBs, as opposed to the usual ovo-cylindrical shape associated with most granuloviruses.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent work conducted on a mutant strain of Adoxophyes orana granulovirus showed that the size and shape of granules (occlusion bodies) are responsible for virus tolerance against UV [ 52 ]. To assess the possible impact of polyhedral morphology on the susceptibility to sunlight exposure observed in our study, we compared the shapes and sizes of OBs in the studied strains.…”
Section: Discussionmentioning
confidence: 99%
“…The Betabaculovirus genus is represented by lepidopteran-specific granuloviruses (GVs) [ 7 , 8 ]. They can be distinguished from nucleopolyhedroviruses (NPVs) from the other three genera ( Alphabaculovirus , Gammabaculovirus , and Deltabaculovirus ) because they are built of smaller, ovo-cylindrical occlusion bodies (OBs) made of granulin (highly conserved structural protein homolog of polyhedrin), that ranges in size from 0.12–0.35 µm in width by 0.3–0.5 µm in length [ 9 ].…”
Section: Introductionmentioning
confidence: 99%